New haplotypes of the Plasmodium falciparum chloroquine resistance transporter (pfcrt) gene among chloroquine-resistant parasite isolates. - Nagesha, H; Casey, G; Rieckmann, K; Fryauff, D; Laksana, B; Reeder, J; Maguire, J; Baird, J (2003)
Mutations in the Plasmodium falciparum chloroquine resistance transporter (pfcrt) gene were examined to assess their associations with chloroquine resistance in clinical samples from Armopa (Papua) and Papua New Guinea. In Papua, two of the five pfcrt haplotypes found were new: SVIET from Armopa and CVIKT from an isolate in Timika. There was also a strong association (P < 0.0001) between the pfcrt 76T allele and chloroquine resistance in 50 samples. In Papua New Guinea, mutations in the pfcrt gene were observed in 15 isolates with chloroquine minimum inhibitory concentrations (MICs) of 16-64 pmol, while the remaining six isolates, which had a wild-type pfcrt gene at codon 76, had MICs of 2-8 pmol. These observations confirm that mutations at codon 76 in the pfcrt gene are present in both in vivo and in vitro cases of chloroquine resistance, and that detection of the pfcrt 76T allele could predict potential chloroquine treatment failures.